Negative electrode active material and electrochemical device and electronic device using the same

By optimizing the graphitization degree and K value of the negative electrode active material, combined with the appropriate crystal size and orientation of the carbon material, the shortcomings of lithium-ion batteries in terms of energy density, cycling performance and rate performance are solved, and the overall performance of the battery is significantly improved.

CN114628625BActive Publication Date: 2024-12-13NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210287385.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-04
Publication Date
2024-12-13
Estimated Expiration
2040-06-04

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in energy density, cycling performance and rate performance, and there are no effective means of improvement.

Method used

By optimizing the graphitization degree and K value of the negative electrode active material, combined with the appropriate crystal size and orientation of the carbon material, a layer of negative electrode active material that meets a specific range is designed and applied in electrochemical devices to improve the performance of lithium-ion batteries. .

Benefits of technology

It significantly improves the energy density, circulation performance and rate performance of lithium-ion batteries, reduces the lithium-ion phenomenon and circulation expansion rate, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628625B_ABST
    Figure CN114628625B_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode active material and an electrochemical device and an electronic device using the negative electrode active material. Specifically, the present application provides a negative electrode active material, which includes a carbon material, wherein the specific peak intensity ratio K of the carbon material and the ratio of the graphitization degree Gr and K are within a specific range. The negative electrode active material of the present application can significantly improve the energy density, cycle performance and rate performance of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention application with the application date of June 4, 2020, application number "202080003323.X", and invention name "Negative electrode active material and electrochemical device and electronic device using the same". Technical Field

[0002] The present application relates to the field of energy storage, and in particular to a negative electrode active material and an electrochemical device and an electronic device using the negative electrode active material. Background Art

[0003] Electrochemical devices (e.g., lithium-ion batteries) are widely used due to their environmental friendliness, high operating voltage, large specific capacity, and long cycle life, and have become the most promising new green chemical power source in the world today. Small-sized lithium-ion batteries are usually used as power sources to drive portable electronic communication devices (e.g., portable cameras, mobile phones, or laptops, etc.), especially high-performance portable devices. Medium-sized and large-sized lithium-ion batteries with high output characteristics are developed for use in electric vehicles (EVs) and large-scale energy storage systems (ESS). With the widespread application of lithium-ion batteries, their energy density, cycle performance, and rate performance have become key technical issues that need to be solved urgently. Improving the active materials in the pole piece is one of the research directions to solve the above problems.

[0004] In view of the above, there is a real need to provide an improved negative electrode active material and an electrochemical device and an electronic device using the same. Summary of the invention

[0005] The embodiments of the present application provide a negative electrode active material and an electrochemical device and an electronic device using the negative electrode active material to solve at least one problem existing in the related art to at least some extent.

[0006] According to one aspect of the present application, a negative electrode active material is provided, wherein the negative electrode active material comprises a carbon material, wherein the carbon material satisfies the following relationship: 6<Gr / K<16, wherein Gr is the graphitization degree of the carbon material, measured by X-ray diffraction; and K is the graphitization degree of the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of the carbon material at 1500 cm -1 Up to 1650cm -1 The ratio of the peak intensity Ig, Id / Ig, is measured by Raman spectroscopy, and the K is 0.06 to 0.15.

[0007] In some embodiments, the carbon material satisfies the following relationship: 8 < Gr / K < 15. In some embodiments, the carbon material satisfies the following relationship: 10 < Gr / K < 12. In some embodiments, the Gr / K value of the carbon material is 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5 or in the range formed by any two of the above values.

[0008] In some embodiments, the K of the carbon material is 0.08 to 0.10. In some embodiments, the K of the carbon material is 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or in the range of any two of the above values.

[0009] According to an embodiment of the present application, the graphitization degree Gr of the carbon material is 0.92 to 0.96. In some embodiments, the graphitization degree Gr of the carbon material is 0.92, 0.93, 0.94, 0.95, 0.96 or within the range of any two of the above values.

[0010] According to an embodiment of the present application, the carbon material satisfies at least one of the following relationships:

[0011] Lc / S<9;

[0012] La / S>20,

[0013] in:

[0014] La is the crystal size of the carbon material crystal along the horizontal axis measured by X-ray diffraction, in nm;

[0015] Lc is the crystal size of the carbon material crystal along the vertical axis measured by X-ray diffraction, in nm;

[0016] S is the ratio of the peak area C004 of the (004) plane and the peak area C110 of the (110) plane of the negative electrode active material measured by X-ray diffraction spectrum;

[0017] The Lc is less than 45, and the La is greater than 50.

[0018] In some embodiments, Lc / S is less than 8. In some embodiments, Lc / S is less than 7. In some embodiments, Lc / S is less than 6. In some embodiments, Lc / S is greater than 2. In some embodiments, Lc / S is greater than 3. In some embodiments, Lc / S is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, or in a range consisting of any two of the above endpoints.

[0019] In some embodiments, La / S>22. In some embodiments, La / S>25. In some embodiments, La / S>28. In some embodiments, La / S>30. In some embodiments, La / S<60. In some embodiments, La / S<55. In some embodiments, La / S<50. In some embodiments, La / S is 22, 25, 28, 30, 35, 40, 45, 50 or in a range consisting of any two of the above endpoints.

[0020] In some embodiments, the Lc is less than 40. In some embodiments, the Lc is less than 35. In some embodiments, the Lc is less than 30. In some embodiments, the Lc is less than 25. In some embodiments, the Lc is greater than 10. In some embodiments, the Lc is greater than 15. In some embodiments, the Lc is greater than 20. In some embodiments, the Lc is 20, 22, 25, 28, 30, 35, 40, 43, or within the range of any two of the above values.

[0021] In some embodiments, La is greater than 60. In some embodiments, La is greater than 80. In some embodiments, La is greater than 100. In some embodiments, La is greater than 110. In some embodiments, La is greater than 120. In some embodiments, La is greater than 130. In some embodiments, La is greater than 150. In some embodiments, La is greater than 180. In some embodiments, La is greater than 200. In some embodiments, La is greater than 220. In some embodiments, La is less than 300. In some embodiments, La is less than 250. In some embodiments, La is 55, 60, 70, 80, 90, 100, 120, 150, 180, 200, 230, 250, or within the range of any two of the above values.

[0022] According to an embodiment of the present application, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>23.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>25.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>28.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>30.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<50.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<45.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<40.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<35.0. In some embodiments, the Dv10 value and the Dv90 value Dv90 / Dv10+Dv90 of the negative electrode active material are 24, 26, 28, 30, 33, 35 or within the range of any two of the above values. In the above relationship, the units of Dv90 and Dv10 are μm.

[0023] According to another aspect of the present application, the present application provides an electrochemical device, which includes a positive electrode, an electrolyte and a negative electrode, the negative electrode includes a negative electrode active material layer and a current collector, and the negative electrode active material layer includes the negative electrode active material according to the present application.

[0024] According to an embodiment of the present application, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 To 0.121mg / mm 2 The compaction density of the negative electrode active material layer is 1.70 g / cm 3 Up to 1.92g / cm 3 .

[0025] In some embodiments, the surface density of the negative electrode active material layer is 0.080 mg / mm 2 Up to 0.120mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.085 mg / mm 2 To 0.110mg / mm 2In some embodiments, the surface density of the negative electrode active material layer is 0.090 mg / mm 2 Up to 0.100mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 、0.080mg / mm 2 , 0.085mg / mm 2 、0.090mg / mm 2 , 0.095mg / mm 2 , 0.100mg / mm 2 , 0.105mg / mm 2 、0.110mg / mm 2 、0.115mg / mm 2 、0.120mg / mm 2 、0.121mg / mm 2 Or within the range of any two of the above values.

[0026] In some embodiments, the compaction density of the negative electrode active material layer is 1.75 g / cm 3 Up to 1.90g / cm 3 In some embodiments, the compaction density of the negative electrode active material layer is 1.80 g / cm 3 Up to 1.85g / cm 3 In some embodiments, the compaction density of the negative electrode active material layer is 1.70 g / cm 3 , 1.75g / cm 3 , 1.78g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 , 1.85g / cm 3 、1.88g / cm 3 , 1.90g / cm 3 、1.92g / cm 3 Or within the range of any two of the above values.

[0027] According to an embodiment of the present application, in a fully charged state, the ratio S' of the peak area C004' of the (004) plane and the peak area C110' of the (110) plane of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 10 to 20. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 12 to 18. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 14 to 16. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or in the range of any two of the above values.

[0028] According to an embodiment of the present application, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6N / m to 15N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 8N / m to 14N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 10N / m to 12N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6N / m, 7N / m, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m or within the range of any two of the above values.

[0029] According to an embodiment of the present application, the negative electrode active material layer has a porosity of 20% to 40%. In some embodiments, the negative electrode active material layer has a porosity of 25% to 35%. In some embodiments, the negative electrode active material layer has a porosity of 28% to 32%. In some embodiments, the porosity of the negative electrode active material layer is 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or within the range of any two of the above values.

[0030] According to an embodiment of the present application, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 280°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 300°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 320°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 340°C.

[0031] According to an embodiment of the present application, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 130°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 140°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 150°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 160°C.

[0032] According to yet another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.

[0033] Additional aspects and advantages of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0035] Figure 1 A scanning electron microscope (SEM) image of the negative electrode active material used in Comparative Example 2 at a magnification of 500 times is shown.

[0036] Figure 2 A scanning electron microscope (SEM) image of the negative electrode active material used in Example 5 at a magnification of 500 times is shown.

[0037] Figure 3 The photograph of the appearance of the negative electrode active material used in Example 5 after cycling is shown, in which there is no lithium deposition phenomenon.

[0038] Figure 4 A photograph of the appearance of the negative electrode active material used in Comparative Example 1 after cycling is shown, in which lithium deposition is shown.

[0039] Figure 5 The photograph of the appearance of the negative electrode active material used in Comparative Example 2 after cycling is shown, which shows severe lithium deposition.

[0040] Figure 6 The cycle capacity retention rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 25° C. with the number of cycles are shown.

[0041] Figure 7The cycle capacity retention curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 45° C. with the number of cycles are shown.

[0042] Figure 8 The cyclic expansion rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 25° C. with the number of cycles are shown.

[0043] Fig. 9 The cyclic expansion rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 45° C. with the number of cycles are shown. DETAILED DESCRIPTION

[0044] The embodiments of the present application will be described in detail below. In the present application specification, the same or similar components and components with the same or similar functions are represented by similar reference numerals. The embodiments of the accompanying drawings described herein are illustrative, graphical, and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0045] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0046] With the widespread application of electrochemical devices (e.g., lithium-ion batteries), the requirements for their performance are constantly increasing. Energy density, cycle performance, and rate performance are important indicators for evaluating the performance of lithium-ion batteries. So far, no effective means have been developed to simultaneously improve the energy density, cycle performance, and rate performance of lithium-ion batteries.

[0047] The present application solves the above problems by optimizing the negative electrode active material. Specifically, the present application provides a negative electrode active material, the negative electrode active material comprises a carbon material, wherein the carbon material satisfies the following relationship: 6<Gr / K<16; wherein Gr is the graphitization degree of the carbon material, measured by X-ray diffraction; and K is the graphitization degree of the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of the carbon material at 1500 cm -1 Up to 1650cm -1The ratio of the peak intensity Ig, Id / Ig, is measured by Raman spectroscopy, and the K is 0.06 to 0.15.

[0048] In some embodiments, the graphitization degree Gr and K of the carbon material meet the following relationship: 8<Gr / K<15. In some embodiments, the graphitization degree Gr and K of the carbon material meet the following relationship: 10<Gr / K<12. In some embodiments, the ratio of the graphitization degree Gr and K of the carbon material Gr / K is 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5 or in the range of any two of the above values.

[0049] In some embodiments, the K of the carbon material is 0.08 to 0.10. In some embodiments, the K of the carbon material is 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or in the range of any two of the above values.

[0050] The K of carbon materials can characterize the proportion of surface defects and crystalline regions of the materials. K can be measured by Raman spectroscopy: using a 523nm light source (shading intensity 5%), sampling 100 points in an area of ​​100μm×100μm, and calculating the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of carbon materials at 1500 cm -1 Up to 1650cm -1 The ratio of the peak intensity Ig and the average value are the K value of the carbon material.

[0051] The "graphitization degree" of carbon materials refers to the degree to which non-graphite carbon is transformed into graphite-like carbon at high temperature or during secondary heating. The graphitization degree of carbon materials can be obtained by the following method: using high-purity silicon powder as an internal standard calibration, testing the interplanar spacing (d002) of the 002 plane of the carbon material by X-ray diffraction method, and calculating the graphitization degree Gr of the carbon material according to the following formula: Gr = (0.344-d002) / 0.086×100%.

[0052] The graphitization degree and K value of the carbon material in the negative electrode active material will affect the embedding and de-embedding of lithium ions. For example, during the cyclic discharge process of a lithium-ion battery, lithium ions migrate to the negative electrode, and the negative electrode will accept lithium ions. The graphitization degree and K value of the carbon material will affect the speed at which lithium ions are embedded in the carbon material particles. Under the condition of high-rate discharge, if the lithium ions cannot be quickly embedded in the carbon material particles and diffuse in them, the lithium ions will precipitate on the surface, accelerating the cyclic decay of the lithium-ion battery. During the cyclic charging process of the lithium-ion battery, lithium ions are extracted from the negative electrode. If the lithium ions cannot quickly escape from the negative electrode, they will form dead lithium inside the carbon material particles, which will also accelerate the cyclic decay of the lithium-ion battery. The graphitization degree and K value of the carbon material will also affect the thickness of the solid electrolyte interface (SEI) film formed during the first cycle of the lithium-ion battery, thereby affecting the first coulomb efficiency of the lithium-ion battery, and then affecting the energy density of the lithium-ion battery.

[0053] When the carbon material has a higher degree of graphitization (e.g., Gr>0.96), the interplanar spacing of the carbon material decreases, which is not conducive to the extraction of lithium ions from the carbon material. When the carbon material has a lower degree of graphitization (e.g., Gr<0.92), the SP 3 There are more bonds, which restrain the layers of the carbon material from each other, making the structure of the carbon material more stable.

[0054] When the graphitization degree Gr of the carbon material and the ratio Gr / K of the graphitization degree of the carbon material to K are within the above ranges, the lithium ion battery has significantly improved energy density, cycle performance, and rate performance.

[0055] According to an embodiment of the present application, the graphitization degree Gr of the carbon material is 0.92 to 0.96. In some embodiments, the graphitization degree Gr of the carbon material is 0.92, 0.93, 0.94, 0.95, 0.96 or in the range of any two of the above values. When the graphitization degree of the carbon material is within the above range, it helps to further improve the energy density, cycle performance and rate performance of the lithium-ion battery.

[0056] According to an embodiment of the present application, the carbon material satisfies at least one of the following relationships:

[0057] Lc / S<9;

[0058] La / S>20,

[0059] in:

[0060] La is the crystal size of the carbon material crystal along the horizontal axis measured by X-ray diffraction, in nm;

[0061] Lc is the crystal size of the carbon material crystal along the vertical axis measured by X-ray diffraction, in nm;

[0062] S is the ratio of the peak area C004 of the (004) plane and the peak area C110 of the (110) plane of the negative electrode active material measured by X-ray diffraction spectrum;

[0063] The Lc is less than 45, and the La is greater than 50.

[0064] In some embodiments, Lc / S is less than 8. In some embodiments, Lc / S is less than 7. In some embodiments, Lc / S is less than 6. In some embodiments, Lc / S is greater than 2. In some embodiments, Lc / S is greater than 3. In some embodiments, Lc / S is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, or in a range consisting of any two of the above endpoints.

[0065] In some embodiments, La / S>22. In some embodiments, La / S>25. In some embodiments, La / S>28. In some embodiments, La / S>30. In some embodiments, La / S<60. In some embodiments, La / S<55. In some embodiments, La / S<50. In some embodiments, La / S is 22, 25, 28, 30, 35, 40, 45, 50 or in a range consisting of any two of the above endpoints.

[0066] In some embodiments, the Lc is less than 40. In some embodiments, the Lc is less than 35. In some embodiments, the Lc is less than 30. In some embodiments, the Lc is less than 25. In some embodiments, the Lc is greater than 10. In some embodiments, the Lc is greater than 15. In some embodiments, the Lc is greater than 20. In some embodiments, the Lc is 20, 22, 25, 28, 30, 35, 40, 43, or within the range of any two of the above values.

[0067] In some embodiments, La is greater than 60. In some embodiments, La is greater than 80. In some embodiments, La is greater than 100. In some embodiments, La is greater than 110. In some embodiments, La is greater than 120. In some embodiments, La is greater than 130. In some embodiments, La is greater than 150. In some embodiments, La is greater than 180. In some embodiments, La is greater than 200. In some embodiments, La is greater than 220. In some embodiments, La is less than 300. In some embodiments, La is less than 250. In some embodiments, La is 55, 60, 70, 80, 90, 100, 120, 150, 180, 200, 230, 250, or within the range of any two of the above values.

[0068] The crystal size of carbon material crystals will affect the embedding and de-embedding of lithium ions during the cycle. According to the X-ray diffraction pattern, the ratio S of the peak area C004 of the (004) plane of the negative electrode active material and the peak area C110 of the (110) plane can characterize the orientation of the negative electrode active material. The larger S is, the greater the anisotropy of the negative electrode active material. The smaller S is, the greater the isotropy of the negative electrode active material. When the crystal size of the carbon material and its ratio to the orientation are within the above range, it helps to further improve the energy density, cycle performance and rate performance of lithium-ion batteries.

[0069] According to an embodiment of the present application, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>23.0, and the units of Dv90 and Dv10 are μm. "Dv90" refers to the particle size of the negative electrode active material in the volume-based particle size distribution from the small particle size side to reach 90% of the volume accumulation, that is, the volume of the negative electrode active material smaller than this particle size accounts for 90% of the total volume of the negative electrode active material. "Dv10" refers to the particle size of the negative electrode active material in the volume-based particle size distribution from the small particle size side to reach 10% of the volume accumulation, that is, the volume of the negative electrode active material smaller than this particle size accounts for 10% of the total volume of the negative electrode active material. The particle size of the negative electrode active material can be obtained by testing with a particle size tester (e.g., Malvern particle size tester).

[0070] In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>25.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>28.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90>30.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<50.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<45.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<40.0. In some embodiments, the Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10+Dv90<35.0. In some embodiments, the Dv90 / Dv10+Dv90 of the negative electrode active material is 24, 26, 28, 30, 33, 35 or within the range of any two of the above values. In the above relationship, the units of Dv90 and Dv10 are μm.

[0071] When the particle size of the negative electrode active material is large, the specific surface area of ​​the negative electrode active material is small, so that the lithium-ion battery only needs to consume less lithium ions to form a solid electrolyte interface (SEI) film with the electrolyte during the first cycle, thereby improving the first coulombic efficiency of the lithium-ion battery. A larger particle size will also extend the path of lithium ion insertion and deinsertion, thereby reducing the kinetic performance of the lithium-ion battery. In addition, a larger particle size will also have an adverse effect on the cyclic expansion of the lithium-ion battery. Conversely, when the particle size of the negative electrode active material is small, the specific surface area of ​​the negative electrode active material is large, so that the lithium-ion battery needs to consume more lithium ions to form a SEI film with the electrolyte during the first cycle, thereby reducing the first coulombic efficiency of the lithium-ion battery. A smaller particle size will also shorten the path of lithium ion insertion and deinsertion, thereby affecting the kinetic performance of the lithium-ion battery. In addition, a smaller particle size will also have an adverse effect on the cyclic expansion of the lithium-ion battery. When the Dv90 and Dv10 of the negative electrode active material meet the above relationship, it is helpful to balance the various properties of the ion battery and further improve the energy density, cycle performance and rate performance of the lithium-ion battery.

[0072] The present application also provides an electrochemical device, which includes a positive electrode, a negative electrode, a separator and an electrolyte. The following description can be used for the positive electrode, the negative electrode, the separator and the electrolyte in the present application.

[0073] negative electrode

[0074] The negative electrode used in the electrochemical device of the present application includes a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer includes the negative electrode active material described in the present application.

[0075] According to an embodiment of the present application, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 To 0.121mg / mm 2 The compaction density of the negative electrode active material layer is 1.70 g / cm 3 Up to 1.92g / cm 3 .

[0076] In some embodiments, the surface density of the negative electrode active material layer is 0.080 mg / mm 2 Up to 0.120mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.085 mg / mm 2 To 0.110mg / mm 2 In some embodiments, the surface density of the negative electrode active material layer is 0.090 mg / mm 2 Up to 0.100mg / mm2 In some embodiments, the surface density of the negative electrode active material layer is 0.077 mg / mm 2 、0.080mg / mm 2 、0.085mg / mm 2 , 0.090mg / mm 2 , 0.095mg / mm 2 , 0.100mg / mm 2 , 0.105mg / mm 2 、0.110mg / mm 2 、0.115mg / mm 2 、0.120mg / mm 2 、0.121mg / mm 2 Or within the range of any two of the above values. The surface density of the negative electrode active material layer can be tested by the following method: discharge the battery to 0 SOC%, disassemble the battery, clean, dry, use an electronic balance to weigh a certain area A of the negative electrode (the negative electrode current collector is coated with a negative electrode active material layer on both sides), and the weight is recorded as W1; use a solvent to wash off the negative electrode active material layer, dry, and measure the weight of the negative electrode current collector, which is recorded as W2. The surface density of the negative electrode active material layer is calculated by the following formula: (W1-W2) / (A×2).

[0077] In some embodiments, the compaction density of the negative electrode active material layer is 1.75 g / cm 3 Up to 1.90g / cm 3 In some embodiments, the compaction density of the negative electrode active material layer is 1.80 g / cm 3 Up to 1.85g / cm 3 In some embodiments, the compaction density of the negative electrode active material layer is 1.70 g / cm 3 , 1.75g / cm 3 , 1.78g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 , 1.85g / cm 3 、1.88g / cm 3 , 1.90g / cm 3 , 1.92g / cm 3Or within the range of any two of the above values. The compaction density of the negative electrode active material layer can be tested by the following method: discharge the battery to 0SOC%, disassemble the battery, clean, dry, use an electronic balance to weigh a certain area A of the negative electrode (the negative electrode current collector is coated with a negative electrode active material layer on both sides), the weight is recorded as W1, and the thickness T1 of the negative electrode is measured using a micrometer. Wash off the negative electrode active material layer with a solvent, dry it, measure the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. The weight W0 and thickness T0 of the negative electrode active material layer arranged on one side of the negative electrode current collector and the compaction density of the negative electrode active material layer are calculated by the following formula:

[0078] W0=(W1-W2) / 2

[0079] T0=(T1-T2) / 2

[0080] Compacted density = W0 / (T0×A).

[0081] According to an embodiment of the present application, in a fully charged state, the ratio S' of the peak area C004' of the (004) plane and the peak area C110' of the (110) plane of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 10 to 20. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 12 to 18. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is in the range of 14 to 16. In some embodiments, in a fully charged state, the S' of the negative electrode active material layer measured by the X-ray diffraction spectrum is 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or in the range of any two of the above values. S' can characterize the orientation of the negative electrode active material layer. The larger S' is, the greater the anisotropy of the negative electrode active material layer is. The smaller S' is, the greater the isotropy of the negative electrode active material layer is.

[0082] According to an embodiment of the present application, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6N / m to 15N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 8N / m to 14N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 10N / m to 12N / m. In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is 6N / m, 7N / m, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m or within the range of any two of the above values.

[0083] The peel strength between the negative electrode active material layer and the negative electrode current collector can be obtained by tensile testing, as follows: Use an Instron (model 33652) tester to test the adhesion between the negative electrode active material layer and the negative electrode current collector: take a 15-20 mm long electrode sheet, fix it on a steel plate with 3M double-sided tape, stick the tape on the surface of the negative electrode active material layer, and connect one side of the tape to a paper tape of the same width. Adjust the limit block of the tensile testing machine to a suitable position, fold the paper tape upward and slide 40 mm, with a sliding rate of 50 mm / min, and test the peel strength between the negative electrode active material layer and the negative electrode current collector at 180° (i.e., stretching in the opposite direction).

[0084] According to an embodiment of the present application, the negative electrode active material layer has a porosity of 20% to 40%. In some embodiments, the negative electrode active material layer has a porosity of 25% to 35%. In some embodiments, the negative electrode active material layer has a porosity of 28% to 32%. In some embodiments, the porosity of the negative electrode active material layer is 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or within the range of any two of the above values. The porosity of the negative electrode active material layer can be obtained according to the standard test of "GB / T24586-2009 Determination of Apparent Density, True Density and Porosity of Iron Ore".

[0085] When the surface density of the negative electrode active material layer is constant, reducing the compaction density of the negative electrode active material layer will reduce the anisotropy and porosity of the negative electrode active material layer and reduce the peel strength between the negative electrode active material layer and the negative electrode current collector. When the compaction density of the negative electrode active material layer is constant, reducing the surface density of the negative electrode active material layer will increase the anisotropy of the negative electrode active material layer, reduce the porosity of the negative electrode active material layer and reduce the peel strength between the negative electrode active material layer and the negative electrode current collector. When the surface density, compaction density, orientation degree S', porosity and / or peel strength between the negative electrode active material and the negative electrode current collector of the negative electrode active material are within the above range, it helps to further improve the energy density, cycle performance and rate performance of the lithium-ion battery.

[0086] According to an embodiment of the present application, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 280°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 300°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 320°C. In some embodiments, when the electrochemical device is fully charged, the thermal decomposition temperature of the negative electrode active material layer is not less than 340°C. When the electrochemical device is in a fully charged state, lithium ions are embedded in the vacancies of the negative electrode material. At this time, the thermal decomposition temperature of the negative electrode active material layer can represent the degree of high temperature aging of the negative electrode, that is, the higher the decomposition temperature of the negative electrode active material, the milder its degree of high temperature aging, and the good high temperature cycle performance of the lithium ion battery.

[0087] According to an embodiment of the present application, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is not less than 130°C. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is not less than 140°C. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is not less than 150°C. In some embodiments, when the electrochemical device is fully discharged, the thermal decomposition temperature of the negative electrode active material layer is not less than 160°C. When the electrochemical device is in a fully discharged state, all lithium ions are released from the negative electrode, and the thermal decomposition temperature of the negative electrode active material layer can indirectly characterize the stability of the SEI film, that is, the higher the decomposition temperature of the negative electrode active material, the better the thermal stability of the SEI film, the less lithium ions are consumed to repair the SEI film during the lithium ion battery cycle, and the better the cycle performance of the lithium ion battery.

[0088] The thermal decomposition temperature of the negative electrode active material layer can be measured by differential scanning calorimetry (DSC). Specifically, a differential scanning calorimeter is used to heat the negative electrode active material layer to be tested at a constant heating rate at 0-800°C.

[0089] The negative electrode current collector used in the present application may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0090] According to an embodiment of the present application, the negative electrode further includes a conductive layer. In some embodiments, the conductive material of the conductive layer may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0091] According to an embodiment of the present application, the negative electrode further includes a binder, and the binder is selected from at least one of the following: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.

[0092] positive electrode

[0093] The positive electrode includes a positive electrode current collector and a positive electrode active material disposed on the positive electrode current collector. The specific types of the positive electrode active material are not subject to specific restrictions and can be selected according to needs.

[0094] In some embodiments, the positive electrode active material includes a positive electrode material capable of absorbing and releasing lithium (Li). Examples of positive electrode materials capable of absorbing / releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.

[0095] Specifically, the chemical formula of lithium cobalt oxide may be as shown in Chemical Formula 1:

[0096] Li x Co a M1 b O 2-c Chemical formula 1

[0097] Wherein M1 represents at least one selected from nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr) and silicon (Si), and the values ​​of x, a, b and c are respectively in the following ranges: 0.8≤x≤1.2, 0.8≤a≤1, 0≤b≤0.2, -0.1≤c≤0.2.

[0098] The chemical formula of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide may be as shown in Chemical Formula 2:

[0099] Li y Ni d M2 e O 2-f Chemical formula 2

[0100] Wherein M2 represents at least one selected from cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr) and silicon (Si), and the values ​​of y, d, e and f are respectively in the following ranges: 0.8≤y≤1.2, 0.3≤d≤0.98, 0.02≤e≤0.7, -0.1≤f≤0.2.

[0101] The chemical formula of lithium manganate can be as shown in Chemical Formula 3:

[0102] Li z Mn 2-g M3 g O 4-h Chemical formula 3

[0103] Wherein M3 represents at least one selected from cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr) and tungsten (W), and the values ​​of z, g and h are respectively in the following ranges: 0.8≤z≤1.2, 0≤g<1.0 and -0.2≤h≤0.2.

[0104] In some embodiments, the weight of the positive electrode active material layer is 1.5 to 15 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 3 to 10 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 5 to 8 times the weight of the negative electrode active material layer. In some embodiments, the weight of the positive electrode active material layer is 1.5 times, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, or 15 times the weight of the negative electrode active material layer.

[0105] In some embodiments, the positive electrode active material layer may have a coating on the surface, or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous or crystalline. The coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, F, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.

[0106] In some embodiments, the positive electrode active material layer further includes a binder, and optionally also includes a positive electrode conductive material.

[0107] The binder can improve the bonding between the positive electrode active material particles and also improve the bonding between the positive electrode active material and the current collector. Non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc.

[0108] The positive electrode active material layer includes a positive electrode conductive material to impart conductivity to the electrode. The positive electrode conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of positive electrode conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0109] The positive electrode current collector used in the electrochemical device according to the present application may be aluminum (Al), but is not limited thereto.

[0110] Electrolyte

[0111] The electrolyte that can be used in the embodiments of the present application can be an electrolyte known in the prior art.

[0112] The electrolytes that can be used in the electrolyte of the embodiments of the present application include, but are not limited to: inorganic lithium salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, etc.; fluorine-containing organic lithium salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, LiN(CF3SO2)(C4F9S O2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. In addition, the above electrolytes can be used alone or in combination of two or more. In some embodiments, the electrolyte includes a combination of LiPF6 and LiBF4. In some embodiments, the electrolyte includes a combination of an inorganic lithium salt such as LiPF6 or LiBF4 and a fluorine-containing organic lithium salt such as LiCF3SO3, LiN(CF3SO2)2, or LiN(C2F5SO2)2. In some embodiments, the electrolyte includes LiPF6.

[0113] In some embodiments, the concentration of the electrolyte is in the range of 0.8mol / L to 3mol / L, for example, in the range of 0.8mol / L to 2.5mol / L, in the range of 0.8mol / L to 2mol / L, in the range of 1mol / L to 2mol / L, and for example, 1mol / L, 1.15mol / L, 1.2mol / L, 1.5mol / L, 2mol / L or 2.5mol / L.

[0114] The solvents that can be used in the electrolyte of the embodiments of the present application include, but are not limited to, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, or chain ethers.

[0115] In some embodiments, the cyclic carbonates include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate.

[0116] In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0117] In some embodiments, the linear carbonates include, but are not limited to: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate and the like; as fluorine-substituted linear carbonates, for example, bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate and 2,2,2-trifluoroethyl methyl carbonate.

[0118] In some embodiments, the cyclic carboxylic acid esters include, but are not limited to, γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid esters may be substituted with fluorine.

[0119] In some embodiments, chain carboxylates include, but are not limited to: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate. In some embodiments, part of the hydrogen atoms of chain carboxylates may be substituted by fluorine. In some embodiments, fluorine-substituted chain carboxylates include, but are not limited to: methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate.

[0120] In some embodiments, cyclic ethers include, but are not limited to, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl 1,3-dioxolane, 4-methyl 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.

[0121] In some embodiments, the chain ethers include, but are not limited to, dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane.

[0122] In some embodiments, the solvent used in the electrolyte of the present application includes one or more of the above. In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from a group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, or a combination thereof.

[0123] Additives that can be used in the electrolyte of the embodiments of the present application include, but are not limited to, cyclic carbonates containing carbon-carbon double bonds and compounds containing sulfur-oxygen double bonds.

[0124] In some embodiments, the cyclic carbonate having a carbon-carbon double bond specifically includes, but is not limited to, at least one of vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, vinyl vinyl ethylene carbonate, or 1,2-dimethyl vinylene carbonate.

[0125] In some embodiments, the compound containing a sulfur-oxygen double bond includes, but is not limited to, at least one of vinyl sulfate, 1,2-propylene glycol sulfate, 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, or 3-fluoro-1,3-propane sultone.

[0126] Isolation film

[0127] In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0128] For example, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected. The porous structure can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece.

[0129] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0130] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from one or a combination of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0131] The polymer layer contains polymers, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0132] Electrochemical Devices

[0133] The present application also provides an electrochemical device, which includes a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode includes a positive electrode active material layer and a positive electrode current collector, the negative electrode includes a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer includes the negative electrode active material described in the present application.

[0134] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0135] Electronic Devices

[0136] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0137] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium ion capacitors, etc.

[0138] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0139] Example

[0140] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0141] 1. Preparation of lithium-ion batteries

[0142] 1. Preparation of negative electrode

[0143] The artificial graphite is crushed, graded and sieved to control the particle size distribution so that Dv90 is less than 25 μm to obtain primary particles. A binder is added to the primary particles for bonding, and graded and sieved to control the particle size so that Dv90 is less than 45 μm to obtain secondary particles. The primary particles and the secondary particles are graphitized at 2300-3500°C, and then the treated primary particles and the secondary particles are mixed and sieved to obtain a graphite negative electrode material.

[0144] The graphite negative electrode material, additive, binder styrene butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) prepared above are mixed in a weight ratio of 97:1.51.5, and fully stirred and mixed in an appropriate amount of deionized water to form a uniform negative electrode slurry without sedimentation. The negative electrode slurry is coated on the negative electrode current collector (copper foil), dried and cold pressed to obtain a negative electrode active material layer, and then cut and slit to obtain a negative electrode.

[0145] The graphitization degree and K of the graphite material in the negative electrode can be controlled by the raw material, particle size, graphitization treatment temperature and the ratio of primary particles to secondary particles.

[0146] 2. Preparation of positive electrode

[0147] Lithium cobalt oxide (Li x Co a M1 b O 2-c , x, a, b and c values ​​are respectively in the following ranges: 0.8≤x≤1.2, 0.8≤a≤1, 0≤b≤0.2, -0.1≤c≤0.2; M1 is manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo) and combinations thereof), acetylene black and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent in a weight ratio of 95:2:3 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut and slit to obtain a positive electrode.

[0148] 3. Preparation of electrolyte

[0149] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a weight ratio of 1:1:1, and then 2% of fluoroethylene carbonate, 2% of 1,3-propane sultone and 2% of succinonitrile were added. After dissolving and stirring thoroughly, lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte in which the concentration of LiPF6 was 1 mol / L.

[0150] 4. Preparation of isolation membrane

[0151] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0152] 5. Preparation of lithium-ion batteries

[0153] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is placed between the positive electrode and the negative electrode to play an isolating role, and then they are wound to obtain a bare cell; after welding the pole ears, the bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a lithium-ion battery is obtained.

[0154] 2. Test Method

[0155] 1. Test method of K value of carbon materials

[0156] According to Raman spectroscopy, a 523 nm light source (shading intensity of 5%) was used to sample 100 points in a 100 μm × 100 μm area and calculate the carbon material at 1250 cm -1 Up to 1650cm -1 The peak intensity Id of carbon materials at 1500 cm -1 Up to 1650cm-1 The ratio of the peak intensity Ig and the average value are the K value of the carbon material.

[0157] 2. Test method for graphitization degree of carbon materials

[0158] High-purity silicon powder (purity ≥ 99.99%) was used as an internal standard for calibration, and the mixture was mixed according to a weight ratio of carbon material: silicon = 5:1, ground evenly, and pressed into a sheet for sample preparation. The interplanar spacing (d002) of the 002 plane of the carbon material was tested using an X-ray diffractometer (Cu Kα target), and the graphitization degree Gr of the carbon material was calculated by the following formula:

[0159] Gr=(0.344-d002) / 0.086×100%.

[0160] 3. Test method for orientation degree S of negative electrode active material and orientation degree S′ of negative electrode active material layer

[0161] According to the mechanical industry standard JB / T 4220-2011 of the People's Republic of China "Method for Determining Lattice Parameters of Artificial Graphite", the (004) plane diffraction line pattern and the (110) plane diffraction line pattern in the X-ray diffraction spectrum of the negative electrode active material and the negative electrode active material layer are tested. The test conditions are as follows: X-rays are CuKα radiation, and CuKα radiation is removed by a filter or a monochromator. The working voltage of the X-ray tube is 35-45kV, and the working current is 30-50mA. The scanning speed of the counter is 0.3(°) / min. When recording the (004) plane diffraction line pattern, the scanning range of the diffraction angle 2θ is 52°-58°. When recording the (110) plane diffraction line pattern, the scanning range of the diffraction angle 2θ is 70°-79°.

[0162] The peak area of ​​the negative electrode active material obtained from the (004) plane diffraction line pattern is recorded as C004. The peak area of ​​the negative electrode active material obtained from the (110) plane diffraction line pattern is recorded as C110. The ratio of C004 / C110 of the negative electrode active material is calculated and recorded as S.

[0163] The peak area of ​​the negative electrode active material layer obtained from the (004) plane diffraction line pattern is recorded as C004'. The peak area of ​​the negative electrode active material layer obtained from the (110) plane diffraction line pattern is recorded as C110'. The ratio of C004' / C110' of the negative electrode active material is calculated and recorded as S'.

[0164] 4. Testing method for crystal size of carbon materials

[0165] The crystal size La along the horizontal axis and the crystal size Lc along the vertical axis of the carbon material in the test negative electrode active material were analyzed using an X-ray diffractometer.

[0166] 5. Test method for particle size of negative electrode active materials

[0167] The particle size of the negative electrode active material was tested using a Malvern particle size tester: the negative electrode active material was dispersed in an ethanol dispersant, and after ultrasonic treatment for 30 minutes, the sample was added to the Malvern particle size tester to test the Dv90 and Dv10 of the negative electrode active material.

[0168] 6. Test method for surface density of negative electrode active material layer

[0169] The battery is discharged to 0 SOC%, the battery is disassembled, cleaned, and dried. An electronic balance is used to weigh a certain area A of the negative electrode (the negative electrode current collector is coated with a negative electrode active material layer on both sides), and the weight is recorded as W1; the negative electrode active material layer is washed off with a solvent, dried, and the weight of the negative electrode current collector is measured, recorded as W2. The surface density of the negative electrode active material layer is calculated by the following formula: (W1-W2) / (A×2).

[0170] 7. Test method for compaction density of negative electrode active material layer

[0171] Discharge the battery to 0 SOC%, disassemble the battery, clean, dry, and use an electronic balance to weigh a certain area A of the negative electrode (the negative electrode current collector is coated with a negative electrode active material layer on both sides), the weight is recorded as W1, and the thickness T1 of the negative electrode is measured using a micrometer. Use a solvent to wash off the negative electrode active material layer, dry, measure the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Calculate the weight W0 and thickness T0 of the negative electrode active material layer set on one side of the negative electrode current collector and the compaction density of the negative electrode active material layer by the following formula:

[0172] W0=(W1-W2) / 2

[0173] T0=(T1-T2) / 2

[0174] Compacted density = W0 / (T0×A).

[0175] 8. Test method for peel strength between negative electrode active material layer and negative electrode current collector

[0176] Use Instron (model 33652) tensile tester to test the adhesion between the negative electrode active material layer and the negative electrode current collector: take a 15-20 mm long electrode sheet, fix it on a steel plate with 3M double-sided tape, stick the tape on the surface of the negative electrode active material layer, and connect one side of the tape to a paper tape of the same width. Adjust the limit block of the tensile testing machine to a suitable position, fold the paper tape upward and slide 40 mm, with a sliding rate of 50 mm / min, and test the peel strength between the negative electrode active material layer and the negative electrode current collector at 180° (i.e., stretching in the opposite direction).

[0177] 9. Test method for porosity of negative electrode active material layer

[0178] The negative electrode active material layer samples were prepared into complete round pieces. Thirty samples were tested for each embodiment or comparative example, and the volume of each sample was about 0.35 cm 3 The porosity of the negative electrode active material layer was tested according to the standard "GB / T24586-2009 Determination of apparent density, true density and porosity of iron ore".

[0179] 10. Test method for the wetting time of negative electrode active material layer

[0180] 1 mL of electrolyte was dripped onto the negative electrode active material layer and the timing was started. When the electrolyte on the surface of the negative electrode active material layer completely disappeared, the timing was stopped. 100 data were tested for each example or comparative example, and the average value was taken and recorded as the infiltration time of the negative electrode active material layer.

[0181] 11. Test method for thermal decomposition temperature of negative electrode active material layer

[0182] The thermal decomposition temperature of the negative electrode active material layer disassembled in a fully charged or fully discharged state was tested by heating at a constant heating rate of 0-800°C using a differential scanning calorimeter.

[0183] 12. Test method for cycle capacity retention rate of lithium-ion batteries

[0184] At 45°C, let the lithium-ion battery stand for 10 minutes, then charge it to 4.4V at a constant current of 0.7C, discharge it to 0.05C at a constant voltage of 4.4V, and let it stand for 10 minutes. Then charge it to 3.0V at a constant current of 0.7C and let it stand for 10 minutes. This is one cycle, and record the discharge capacity of the first cycle. Repeat the above steps 400 times, and record the discharge capacity after the cycle. The cycle capacity retention rate of the lithium-ion battery is calculated by the following formula:

[0185] Cycle capacity retention rate = (discharge capacity after cycle / discharge capacity of the first cycle) × 100%.

[0186] The cycle capacity retention rate of the lithium-ion battery at 25°C was tested using basically the same steps, except that the operating temperature was 25°C and the number of cycles was 800.

[0187] 13. Test method for cyclic expansion rate of lithium-ion batteries

[0188] At 45°C, let the lithium-ion battery stand for 10 minutes, then charge it to 4.4V at a constant current of 0.7C, discharge it to 0.05C at a constant voltage of 4.4V, and let it stand for 10 minutes. Then charge it to 3.0V at a constant current of 0.7C and let it stand for 10 minutes. This is one cycle, and the thickness of the lithium-ion battery in the first cycle is recorded. Repeat the above steps 400 times, and record the thickness of the lithium-ion battery after the cycle. The cycle expansion rate of the lithium-ion battery is calculated by the following formula:

[0189] Cycle expansion ratio = (thickness after cycle / thickness of first cycle) × 100%.

[0190] The cyclic expansion rate of lithium-ion batteries at 25°C was tested using essentially the same procedure, except that the operating temperature was 25°C and the number of cycles was 800.

[0191] 14. Test method for lithium deposition of lithium-ion batteries

[0192] At 25°C, discharge the lithium-ion battery at a constant current of 0.5C to 3.0V and let it stand for 10 minutes. Then charge it at a constant current of 1.5C to 4.1V, charge it at a constant voltage of 4.1V to 0.05C, charge it at a constant current of 0.7C to 4.3V, charge it at a constant voltage of 4.3V to 0.05C, charge it at a constant current of 0.5C to 4.4V, charge it at a constant voltage of 4.4V to 0.05C, and finally discharge it at a constant current of 0.5C to 3.0V and let it stand for 10 minutes. Repeat the above charging and discharging process 10 times. Disassemble it under dry conditions and take photos to record the state of the negative electrode.

[0193] The degree of lithium plating of lithium-ion batteries is determined according to the following standards:

[0194] When the disassembled negative electrode is golden yellow as a whole, with a very small part being gray, and the area of ​​the gray area is less than 2%, it is determined that no lithium is deposited.

[0195] When most of the negative electrode after disassembly is golden yellow, and gray can be observed in some positions; and the area of ​​the gray area is between 2% and 20%, it is judged to be slight lithium deposition.

[0196] When the disassembled negative electrode appears gray as a whole, with golden color observed in some locations, and the area of ​​the gray area is between 20% and 60%, it is judged to be lithium deposition.

[0197] When the disassembled negative electrode is gray as a whole and the area of ​​the gray region is greater than 60%, it is determined to be severe lithium deposition.

[0198] 3. Test Results

[0199] Table 1 shows the influence of the characteristics of negative electrode active materials on the performance of lithium-ion batteries.

[0200] As shown in Comparative Example 1, when the ratio of the graphitization degree Gr to K of the negative electrode active material is less than 6 and K is greater than 0.15, the initial coulombic efficiency of the lithium-ion battery is very low and lithium precipitation occurs (such as Figure 4 As shown in Comparative Example 2, when the ratio of the graphitization degree Gr to K of the negative electrode active material is greater than 16 and K is less than 0.06, the first coulombic efficiency of the lithium-ion battery is low, and serious lithium precipitation occurs (such as Figure 5 As shown), the cycle capacity retention rate is very low and the cycle expansion rate is very high.

[0201] As shown in Examples 1-36, when the ratio of the graphitization degree Gr to K of the negative electrode active material is in the range of 6 to 16 and K is in the range of 0.06 to 0.15, the initial coulombic efficiency and cycle capacity retention rate of the lithium ion battery can be significantly improved, the cycle expansion rate of the lithium ion battery can be significantly reduced, and the lithium precipitation phenomenon of the lithium ion battery during the cycle process (such as Figure 3 As shown). The significant increase in the first coulombic efficiency indicates that the lithium ion battery has a significantly improved energy density. The significant increase in the cycle capacity retention rate and the significant decrease in the cycle expansion rate indicate that the lithium ion battery has a significantly improved cycle performance. The improvement in the lithium precipitation phenomenon helps to significantly improve the rate performance of the lithium ion battery. Therefore, the lithium ion batteries of Examples 1-36 have significantly improved energy density, cycle performance and rate performance.

[0202] When the graphitization degree Gr of the negative electrode active material is in the range of 0.92 to 0.96, the comprehensive performance is more excellent.

[0203] When the crystal size of the carbon material in the negative electrode active material and the orientation degree of the negative electrode active material satisfy the following relationship: Lc / S<9, La / S>20, Lc<45 and La>50, the first coulombic efficiency, cycle capacity retention rate, cycle expansion rate and / or lithium precipitation phenomenon of the lithium-ion battery can be further improved, thereby enhancing the comprehensive performance of the lithium-ion battery.

[0204] When Dv90 / Dv10+Dv90 is greater than 23.0, it helps to further improve the cycle capacity retention rate and lithium plating phenomenon of lithium-ion batteries, and enhance the overall performance of lithium-ion batteries.

[0205] Figure 1 A scanning electron microscope (SEM) image magnified 500 times of the negative electrode active material used in Comparative Example 2 is shown. As shown in the figure, the negative electrode active material in Comparative Example 2 includes only primary particles. Figure 2A scanning electron microscope (SEM) image magnified 500 times of the negative electrode active material used in Example 5 is shown. As shown in the figure, the negative electrode active material in Example 5 includes a certain ratio of primary particles and secondary particles, and the graphitization degree and K value of the carbon material can be adjusted by adjusting the ratio.

[0206] Figure 6 The cycle capacity retention rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 25° C. with the number of cycles are shown. Figure 7 The cycle capacity retention rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 45°C with the number of cycles are shown. The results show that compared with Comparative Examples 1 and 2, the cycle capacity retention rate of the lithium ion battery of Example 5 at 25°C and 45°C is always maintained above 90%. As the number of cycles increases, the difference in cycle capacity retention rate between Example 5 and Comparative Examples 1 and 2 gradually increases. Figure 8 The cyclic expansion rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 25° C. with the number of cycles are shown. Fig. 9 The cyclic expansion rate curves of the lithium ion batteries of Comparative Example 1, Comparative Example 2 and Example 5 at 45°C with the number of cycles are shown. The results show that compared with Comparative Examples 1 and 2, the cyclic expansion rate of the lithium ion battery of Example 5 at 25°C is always less than 8%, and the cyclic expansion rate at 45°C is always less than 10%. As the number of cycles increases, the difference in cyclic expansion rate between Example 5 and Comparative Examples 1 and 2 gradually increases. The above results show that the lithium ion battery of Example 5 has significantly improved cycle performance during the cycle process at room temperature and high temperature.

[0207] Table 2 shows the influence of the characteristics of the negative electrode active material layer on the performance of the lithium ion battery. Examples 37-44 are improvements based on Example 5 in Table 1, and the only difference between them is the parameters listed in Table 2.

[0208] The results show that when the surface density of the negative electrode active material layer is constant, the comprehensive performance of the battery may also be affected by the compaction density of the negative electrode active material layer, the isotropy of the negative electrode active material layer (S' decreases), the porosity, and the peel strength between the negative electrode active material layer and the negative electrode current collector. 2 To 0.121mg / mm 2 And the compacted density is 1.70g / cm 3 Up to 1.92g / cm 3, the S' of the lithium-ion battery in the fully discharged state is 10 to 20, the peel strength between the negative active material layer and the negative current collector is 6N / m to 15N / m, the porosity of the negative active material layer is 20% to 40%, the thermal decomposition temperature of the negative active material layer in the fully charged state is not less than 280°C, and / or the thermal decomposition temperature of the negative active material layer in the fully discharged state is not less than 130°C, which helps to further improve the initial coulomb efficiency, cycle capacity retention rate, cycle expansion rate and / or lithium precipitation phenomenon of the lithium-ion battery, and enhance the comprehensive performance of the lithium-ion battery. When the compaction density of the negative active material layer is constant, the surface density of the negative active material layer is 0.100mg / mm 2 Lithium-ion batteries have excellent comprehensive performance.

[0209] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0210] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

[0211]

[0212]

[0213]

Claims

1. A negative electrode active material, comprising a carbon material, wherein: The carbon material satisfies at least one of the following relationships: Lc / S < 9; La / S > 20, where: La is the crystal size of the carbon material crystal along the horizontal axis measured by X-ray diffraction method, with the unit of nm; Lc is the crystal size of the carbon material crystal along the vertical axis measured by X-ray diffraction method, with the unit of nm; S is the ratio of the peak area C004 of the (004) plane and the peak area C110 of the (110) plane of the negative electrode active material obtained by measuring the X-ray diffraction pattern; The Lc is less than 45, and the La is greater than 50.

2. The negative electrode active material according to claim 1, wherein The carbon material conforms to the following relationship: 6.1 ≤ Gr / K ≤ 15.3, where Gr is the graphitization degree of the carbon material, measured by X-ray diffraction method, and Gr is 0.92 to 0.96; K is the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of the carbon material at 1500 cm -1 Up to 1650cm -1 The ratio of the peak intensity Ig, Id / Ig, is measured by Raman spectroscopy and K is 0.06 to 0.

15.

3. The negative electrode active material according to claim 1, wherein The Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: Dv90 / Dv10 + Dv90 > 23.0, and the units of Dv90 and Dv10 are μm.

4. An electrochemical device, which includes a positive electrode, an electrolyte, and a negative electrode. The negative electrode includes a negative electrode active material layer and a current collector, and the negative electrode active material layer includes the negative electrode active material according to any one of claims 1 to 3.

5. The electrochemical device according to claim 4, wherein: The surface density of the negative electrode active material layer is 0.077 mg / mm 2 To 0.121mg / mm 2 The compaction density of the negative electrode active material layer is 1.70 g / cm 3 Up to 1.92g / cm 3 .

6. The electrochemical device according to claim 4, wherein: In the fully discharged state, the ratio S' of the peak area C004' of the (004) plane and the peak area C110' of the (110) plane of the negative electrode active material layer measured by the X-ray diffraction pattern is 10 to 20.

7. The electrochemical device according to claim 4, wherein: The peeling strength between the negative electrode active material layer and the negative electrode current collector is 6 N / m to 15 N / m.

8. The electrochemical device according to claim 4, wherein: The negative electrode active material layer has a porosity of 20% to 40%.

9. The electrochemical device according to claim 4, wherein: In the fully charged state of the electrochemical device, the thermal decomposition temperature of the negative electrode active material layer is not less than 280 °C.

10. The electrochemical device according to claim 4, wherein: In the fully discharged state of the electrochemical device, the thermal decomposition temperature of the negative electrode active material layer is not less than 130 °C.

11. The electrochemical device according to claim 4, wherein: The graphitization degree of the carbon material is Gr, and Gr is 0.93 to 0.

95.

12. The electrochemical device according to claim 4, wherein: The carbon material conforms to the following relationship: 7 ≤ Gr / K ≤ 14, Wherein, Gr is the graphitization degree of the carbon material; K is the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of the carbon material at 1500 cm -1 Up to 1650cm -1 The ratio of the peak intensity Ig, Id / Ig, is obtained by Raman spectroscopy.

13. The electrochemical device according to claim 4, wherein: K is 0.07 to 0.14, K is the carbon material at 1250cm -1 Up to 1650cm -1 The peak intensity Id of the carbon material at 1500 cm -1 Up to 1650cm -1 The ratio of the peak intensity Ig, Id / Ig, is obtained by Raman spectroscopy.

14. The electrochemical device according to claim 4, wherein: 3 ≤ Lc / S ≤ 8.

9.

15. The electrochemical device according to claim 4, wherein: 22 ≤ La / S ≤ 45.

16. The electrochemical device according to claim 4, wherein: 15 < Lc ≤ 43.

17. The electrochemical device according to claim 4, wherein: 55 ≤ La ≤ 180.

18. The electrochemical device according to claim 4, wherein: The Dv10 value and the Dv90 value of the negative electrode active material satisfy the following relationship: 23.0 < Dv90 / Dv10 + Dv90 < 50, and the units of Dv90 and Dv10 are μm.

19. The electrochemical device according to claim 18, wherein: 23.0 < Dv90 / Dv10 + Dv90 < 35.

20. An electronic device, which includes the electrochemical device according to any one of claims 4 to 19.